The influence of radio in enhancing farmers’ perceptual situation in problem solving towards insufficient information delivery - Idris Ismail,; Rosidayu Sabran,; Mohd Yahya Mohamed Ariffin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
In Agricultural Extension Services (AES), radio plays a role in situational problems like insufficient infor-mation delivery. Radio not only helps farmers in acquiring information, but also creates a tendency for farmers to deal with informational interaction and to stay connected with the problem. For that rea-son, under structural governance reforms such as decentralisation, radio is expected to have an influ-ence on farmers’ actual perception and opinion in minimising the problem when used in the AES infor-mational delivery process. Drawing upon the Situational Theory Problem Solving (STOPS), this study seeks to determine the role of radio in problem solving (RIPS) on the perceptual situation variables which include problem recognition, constraint recognition, involvement recognition, and referent cri-terion towards solving insufficient information delivery. A total of 400 farmers within AES or the “Rice Bowl” area of Northern Malaysia participated in answering the questionnaire. Data was analysed using the Structural Equation Modelling (SEM). The findings reveal that RIPS plays an important role in influ-encing farmers’ problem recognition, involvement recognition, and referent criterion apart from re-ducing their constraint. As a result, all of the four hypothesised relationships proposed in the study’s conceptual model were significant and supported. Hence, RIPS can now be considered as a joint ele-ment in public communication strategy to deal and solve insufficient information delivery for Malay-sia’s AES.